Efektivitas Pemberian Tablet Fe + Jeruk Manis Dengan Tablet Fe + Pisang Ambon Terhadap Kadar Hb Ibu Hamil Anemia di Klinik Edelweis Medical Centre Kota Tangerang - Abela Mayunita; Rezky Avriliatin (Malahayati Nursing Journal, 2024)
Anemia is a nutritional disorder that is often found and is a major nutritional problem in Indonesia. The Edelweis Medical Center Clinic in Tangerang City in 2021 there will be 26.8% of pregnant women who will experience anemia. In order to meet iron needs, the government through its program provides iron (Fe) tablets at least 90 tablets. One effort to increase Hb levels in anemic pregnant women is by increasing the absorption of iron from foods, such as sweet oranges and Ambon bananas. Knowing the effectiveness of giving Fe tablets + sweet orange with Fe tablets + Ambon banana on Hb levels of anemic pregnant women at the Edelweis Medical Center Clinic in Tangerang City in 2023. Quasy experimental design with pretest-posttest design with control group design. The sample is pregnant women who experience anemia in January-February 2023 at the Edelweis Medical Center Clinic in Tangerang City as many as 34 samples using a purposive sampling technique. The intervention was given 250g once a day for 7 days. Bivariate analysis used paired simple t test and independent t test. The results of the univariate study of Hb levels of pregnant women before administration of Fe tablets + sweet orange averaged = 9.629 gr/dl and after administration of Fe tablets + sweet orange averaged = 11.441gr/dl. Hb levels of pregnant women before administration of Fe tablets + Ambon bananas averaged = 9.635 gr/dl and after administration of Fe tablets + Ambon bananas averaged = 12.118 gr/dl. The bivariate results of the paired simple t test were 0.000 and the independent t test obtained a p value = 0.000.There are differences in Hb levels of anemic pregnant women between Fe tablets + sweet orange and Fe tablets + Ambon bananas. Pregnant women are expected to be diligent in consuming foods that contain iron, one of which is Ambon bananas and sweet oranges so that they can increase Hb levels in the mother's blood, while the process of eating them besides making juice can also be eaten directly. Keywords: Fe Tablets, Ambon Bananas, Sweet Oranges, Hb Levels in Anemia Pregnant Women  ABSTRAK Anemia merupakan salah satu penyakit gangguan gizi yang masih sering ditemukan dan merupakan masalah gizi utama di Indonesia. Klinik Edelweis Medical Centre Kota Tangerang pada tahun 2021 ibu hamil yang mengalami anemia sebanyak 26,8%. Agar dapat memenuhi kebutuhan zat besi, pemerintah melalui programnya memberikan tablet besi (Fe) minimal 90 tablet. Salah satu upaya untuk meningkatkan kadar Hb ibu hamil anemia dengan meningkatkan penyerapan zat besi dari makanan, seperti jeruk manis dan pisang ambon. Mengetahui efektivitas pemberian tablet Fe + jeruk manis dengan tablet Fe + pisang ambon terhadap kadar Hb ibu hamil anemia di Klinik Edelweis Medical Centre Kota Tangerang tahun 2023. Quasy eksperimental desain dengan rancangan pretest-posttest with control group design. Sampel adalah ibu hamil yang mengalami anemia pada bulan Januari-Februari tahun 2023 di Klinik Edelweis Medical Centre Kota Tangerang sebanyak 34 sampel dengan teknik purposive sampling. Intervensi diberikan 1 x sehari 250g selama 7 hari. Analisis bivariat menggunakan uji paired simple t test dan t test independent. Hasil penelitian univariat kadar Hb ibu hamil sebelum pemberian tablet Fe + jeruk manis rata-rata = 9,629 gr/dl dan sesudah pemberian tablet Fe + jeruk manis rata-rata = 11,441gr/dl. Kadar Hb ibu hamil sebelum pemberian tablet Fe + pisang ambon rata-rata = 9,635 gr/dl dan sesudah pemberian tablet Fe + pisang ambon rata-rata = 12,118 gr/dl. Hasil penelitian bivariat uji paired simple t test sebesar 0,000 dan uji t test independent didapatkan nilai p value = 0,000. Terdapat perbedaan kadar Hb ibu hamil anemia antara pemberian tablet Fe + jeruk manis dengan tablet Fe + pisang ambon. Ibu hamil diharapkan rajin mengkonsumsi makanan yang mengandung zat besi salah satunya buah pisang ambon dan jeruk manis agar dapat meningkatkan kadar Hb dalam darah ibu, adapun proses memakannya selain dibuat jus juga boleh dimakan langsung. Kata Kunci: Tablet Fe, Pisang Ambon, Jeruk Manis, Kadar Hb Ibu Hamil Anemia